PCSK9 modulates the Wnt/beta-catenin signaling pathway in myocardial ischemia/reperfusion injury. (3rd October 2022) - Cha, Y; Kim, H E; Jeon, S B; Park, S W; Lee, S H; Lee, C J
Abstract: Background: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a protein that affects cholesterol homeostasis. Recent research has found that PCSK9 has various effects on the heart that are unrelated to LDL cholesterol regulation. The Wnt/β-catenin signaling pathway plays a crucial role during heart development, and it is re-activated in response to cardiac injury. Low-density lipoprotein receptor-related proteins 5 (LRP5) act as co-receptors of Wnt ligands and are indispensable for Wnt/β-catenin signal transduction. However, it is not fully elucidated whether other members of the LDLR-superfamily may be targets of PCSK9. Purpose: This study aimed to determine if LRP5 is a PCSK9 target, study the association between PCSK9 and Wnt/β-catenin signaling, and elucidate its effect on myocardial infarction in patients with ischemic cardiomyopathy. Methods: The expression of Lrp5, phospho-β-catenin, total β-catenin was evaluated by western blot analysis, and the effects of overexpressed PCSK9 were tested under normoxia, hypoxia, or hypoxia/re-oxygenation (H/R) in mouse cardiomyocytes (HL-1). The transcriptional activity of β-catenin was assessed using the TOP-Flash/FOP-Flash luciferase reporter assay. In addition, the impact on various downstream targets of the Wnt/β-catenin signaling pathway was assessed using a quantitative real-time polymerase chain reaction. To examine whether PCSK9 regulates injury of cardiomyocytes in vivo, we subjected transgenic mice with cardiac-specific overexpression of PCSK9 (PCSK9 TG) and wild-type (WT) mice to either sham surgery or ischemia/reperfusion (I/R) surgery. Results: Under hypoxic conditions, the Wnt/β-catenin signaling pathway-related genes were downregulated in HL-1 cells, as evidenced by lower Lrp5 and active phospho-β-catenin expression levels (0.5-fold, n=3, p<0.01). After H/R, the Wnt/β-catenin-related genes were recovered (1.5-fold, p<0.01) in the control group but not in the PCSK9 overexpressed group. In the luciferase reporter assay results, PCSK9 overexpression inhibited the recovery of β-catenin transcriptional activity after H/R, in contrast to the control group. Furthermore, mRNA levels of Axin2, Cyclin D1, which are the Wnt/β-catenin signaling downstream pathway targets, were down-regulated under hypoxia and recovered after H/R but did not recover in PCSK9 overexpressed cells. In the mouse I/R model, the overall protein levels of the Wnt/β-catenin signaling-related genes were down-regulated in PCSK9 TG mice compared to WT mice after I/R injury. Conclusions: These results indicated that the regulation of PCSK9 is closely associated with the Wnt/β-catenin signaling pathway which may play a crucial role in damaged cardiomyocytes. It suggests that the regulation of PCSK9 could be a therapeutic target in patients with ischemic cardiomyopathy. Funding Acknowledgement: Type of funding sources: None.